Insights into Emerging Trends Shaping the Future of Audit and Assurance - Dasinapa, Margaretha Beatrik; Ermawati, Yana (Advances in Managerial Auditing Research, 2024)
The rapid evolution of audit and assurance practices is profoundly influenced by technological advancements, regulatory dynamics, and socio-economic forces. This study aims to investigate the implications of these trends on the audit profession, focusing on the transformative potential of data analytics, artificial intelligence (AI), and blockchain technology. Employing a qualitative literature review methodology, this research synthesizes existing scholarly literature to analyze the current landscape of audit practices comprehensively. Findings reveal that technological innovations, such as data analytics and AI, offer promising opportunities to enhance audit efficiency and effectiveness by enabling auditors to analyze vast amounts of data and detect patterns more efficiently. However, these advancements also present challenges related to data privacy, cybersecurity, and algorithmic interpretation. Regulatory dynamics, including the Sarbanes-Oxley Act (SOX) and the European Union's Audit Reform Directive (ARD), play a crucial role in shaping audit quality and transparency, albeit imposing additional compliance costs on audit firms. Moreover, the expanding scope of assurance services to encompass non-financial reporting and sustainability disclosures underscores the growing importance of auditors' roles in providing assurance on ESG factors. The implications of these trends are far-reaching, necessitating proactive measures from auditors, regulators, and policymakers to address emerging challenges and seize opportunities effectively. Ultimately, advancing knowledge in this field is critical for enhancing audit quality, bolstering stakeholder confidence, and promoting the integrity of corporate reporting practices.